THE LEGAL REGIME ОF INTERNATIONAL HUMANITARIAN ASSISTANCE IN ARMED CONFLICTS - Radivojević, Zoran; Raičević, Nebojša (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The legal regime of international humanitarian assistance provided during armed conflicts is based on several general legal principles. They are guiding principles that apply in all circumstances and situations, regardless of the nature of the armed conflict. The first principle entails that the state has primary responsibility to ensure that the basic needs of population under its jurisdiction are met during the armed conflict. The second principle, closely related to the first one, is the principle that third countries and international humanitarian organizations may offer assistance if a party to the conflict fails to undertake its duty to provide supplies necessary for the survival of the population. The next principles calls for the consent of all concerned parties in the provision of humanitarian assistance, as well as the duty of the parties to the conflict and all third countries to approve and facilitate the unimpeded passage of aid. The last principle is that staff involved in relief operations must be respected and protected.In addition to these general legal principles, international humanitarian assistance is regulated by a dozen of special rules covering various aspects of providing international humanitarian assistance during armed conflict. These rules are the result of a compromise between efforts to provide the vulnerable population with the necessities of life and a demand to protect the sovereignty of all parties to the conflict but particularly of the state in which the aid is being sent. There is a difference between the rules governing humanitarian aid operations in international armed conflicts and the rules applicable in non-international conflicts. The first group of rules is far more numerous; they regulate in detail the issues related to relief actions, including the conditions for passage, delivery and distribution of consignments, the types of goods and services that can be sent, the category of persons who they are intended for, the position of the personnel engaged in these operations, and the technical conditions for implementing these rules.As regards non-international armed conflicts, the rules on humanitarian assistance are fewer, shorter and more general. These scarce rules are sometimes vague, and they mainly come down to the principle of humane treatment and the right of international humanitarian organizations to offer their assistance. Given that non-international conflicts are the predominant form of armed conflict today, there is a strong tendency to extend the application of codified rules of international law governing the provision of humanitarian assistance to these conflicts. The practice of respecting almost all codified rules governing the provision of humanitarian assistance in modern armed conflicts and its wide acceptance by states and other participants confirms that the rules of customary International Humanitarian Law created in this area are applicable in both international and non-international armed conflicts.
Keywords: humanitarian assistance; armed conflicts; international humanitarian law; civil population; Geneva Conventions; Additional Protocols